2012
DOI: 10.1007/s10029-012-0998-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided ilioinguinal/iliohypogastric nerve blocks for chronic pain after inguinal hernia repair

Abstract: Ilioinguinal/iliohypogastric nerve blocks can be effective to treat chronic inguinal pain following surgery of the groin. The use of ultrasound was not superior to nerve stimulator-guided blocks. These blocks could be considered prior to more invasive procedures such as neurectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…Previously, Thomassen et al in 2013 described the use of ultrasound guidance and nerve-stimulator guided blocks for neurectomy. 21 In this paper we present a novel technique that provides the peripheral nerve surgeon a helpful tool to plan and execute the surgery. It is a technique that uses readily available, portable, and cost-effective resources that could be easily implemented to the benefit of many patients with a wide range of peripheral nerve problems.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Thomassen et al in 2013 described the use of ultrasound guidance and nerve-stimulator guided blocks for neurectomy. 21 In this paper we present a novel technique that provides the peripheral nerve surgeon a helpful tool to plan and execute the surgery. It is a technique that uses readily available, portable, and cost-effective resources that could be easily implemented to the benefit of many patients with a wide range of peripheral nerve problems.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report by Thomassen et al,92 the authors found ultrasound-guided IIN/IHN blocks to be effective in treating CPIP with successful prolonged pain relief after a median follow-up time of 20 months. Despite this finding, they reported that they did not find any statistically significant difference in pain outcomes when they compared patients who received nerve-stimulator-guided nerve blocks versus ultrasound-guided nerve blocks.…”
Section: Interventional Pain Managementmentioning
confidence: 98%
“…Few studies have been performed evaluating the efficacy of ultrasound-guided IIN/IHN blocks in the treatment of CPIP, and provide conflicting results 91,92. In a recent report by Thomassen et al,92 the authors found ultrasound-guided IIN/IHN blocks to be effective in treating CPIP with successful prolonged pain relief after a median follow-up time of 20 months.…”
Section: Interventional Pain Managementmentioning
confidence: 99%
“…The method demonstrates superiority and cost-effectiveness when compared with both subarachnoid and general anesthesia [4]. In addition, ilioinguinal nerve block may have a place in the control of chronic pain after inguinal hernia repair [5] and a role in the treatment of chronic pelvic pain [6].…”
Section: Introductionmentioning
confidence: 99%